(untitled) (Research, Society and Development, 2022)
The phytochemical characterization of plants from Brazilian biodiversity is an important tool in the discovery of new bioactive molecules. The objective of this research was to carry out the thermogravimetry out the species, the phytochemical screening and the allelopathic activity of the extracts of the aerial parts of Phoradendron ensifolium. Thermal analysis was carried out from the dried and stabilized plant. The hydroalcoholic extract was obtained by Soxhlet, the aqueous extract was obtained by hot maceration. Secondary metabolites of the class of alkaloids, leucoanthocyanidins, flavonoids, coumarins, anthraquinones, steroids and triterpenes, anthocyanidins, saponins, cyanogenic heterosides, and tannins were researched. The allelopathic activity was evaluated for Lactuca sativa and Allium cepa seeds. Thermal analysis of the plant revealed the safe handling temperature oh the samples to maintain integrity with secondary metabolite compounds. Phytochemical screening was positive for the presence of alkaloids, flavonoids, coumarins, steroids and triterpenes, anthocyanidins, saponins and tannins. The hydroalcoholic extract showed an important allelopathy against monocotyledons and dicotyledonous seeds. The potential reveled by P. ensifolium motivates future studies for complete elucidation and applicability of the species.